Genre and Genesis: Locating Covenants in the Qurʾān and the Bible - Samji, Karim 1978- (2024)
The present article considers the intersection between genre and covenant in scripture in order to locate historical covenants and to trace their complex textual boundaries. Standing on the shoulders of Smith, Wellhausen, and Gunkel, the joint legacy left behind by Martin and Albrecht Noth is equally significant for both Biblical and Islamic studies. Nothian scholarship laid solid foundations for reconstructing the history of tribal traditions. Both of them together created a common frame of reference for studying primary and secondary themes (Themen), literary and documentary forms (Formen), introductory and concluding formulas (Formeln), and theological and political perspectives (Tendenzen), in addition to geographical, transitional, and framing devices (Schemata). In spite of this shared scholarly heritage, it appears that both Biblical and Qurʾānic studies have either been talking at cross-purposes or have reached a critical crossroads, as has happened in the case of covenant. All things considered, genre and tradition criticism allow us to move forward beyond the Methodenstreit in covenant studies.
Keywords: Late Antiquity; Form Criticism; genre criticism; Tradition Criticism; berît; Ṣulḥ